Enteignungsentschadigung. - Dieter Pasternak (De Gruyter Praxishandbuch., 2014)
The present book is written for "on site" practitioners. They will be given an opportunity to acquire information on the fundamental questions of expropriation law and the latest court decisions quickly, comprehensively and reliably. The book deals with the principles for quantifying compensation for expropriated property in key terms in alphabetical order.